The Impact of AI on Computer Science Education. - Shein, Esther (Communications of the ACM, 2024)
The article discusses the impact that artificial intelligence (AI), large language models (LLMs), and tools such as Chat-GPT are having on computer science education and the job market. According to the article, AI and machine learning (ML) will make it less necessary for humans to learn computer programming (coding) in the future. It states that close to 90 percent of all jobs will be impacted in some way by generative AI.